2004
DOI: 10.1007/s00432-003-0521-z
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-complexed adenoviral gene transfer in cancer cells expressing various levels of coxsackievirus and adenovirus receptor

Abstract: Liposome-complexed adenoviral gene transfer appears to depend on lipid composition and the level of liposome uptake by cancer cells, in addition to CAR levels. Our study suggest that these multiple factors should be considered in designing liposome-complexed adenoviral vectors to improve outcomes of current adenoviral cancer gene therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Adenoviral vector-mediated gene manipulation is a potential approach (Song et al, 2007), but CAR-deficiency in some cancer cells prevents effective adenoviral infection of target cells. We previously found to enhance the stability and uptake of liposome-complexed adenovirus in CAR deficient human cancer cell lines (Lee et al, 2004). In this study we demonstrated that the problem of CAR-deficiency, can be overcome by complexing the adenovirus with PEGPE in vitro as well as in vivo in a mouse metastasis model we established, by injecting syngenetic mice with CAR-deficient CT-26 mouse colon cancer cells.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Adenoviral vector-mediated gene manipulation is a potential approach (Song et al, 2007), but CAR-deficiency in some cancer cells prevents effective adenoviral infection of target cells. We previously found to enhance the stability and uptake of liposome-complexed adenovirus in CAR deficient human cancer cell lines (Lee et al, 2004). In this study we demonstrated that the problem of CAR-deficiency, can be overcome by complexing the adenovirus with PEGPE in vitro as well as in vivo in a mouse metastasis model we established, by injecting syngenetic mice with CAR-deficient CT-26 mouse colon cancer cells.…”
Section: Discussionmentioning
confidence: 68%
“…We demonstrated previously that addition of PEGPE enhances the stability and uptake of liposomecomplexed adenovirus in CAR deficient human cancer cell lines (Lee et al, 2004). Here we investigated the effect of liposome dose on the efficiency of liposome-complexed adenoviral gene transfer in CAR deficient CT-26 cell lines.…”
Section: Adenoviral Gene Expression In Car Deficient Cells By Liposommentioning
confidence: 95%
“…42 PEG incorporation into DOTAP liposome-enhanced stability and uptake of liposome-complexed adenoviral and further improved the infection efficiency regardless of infection conditions and reported that in CAR-deficient cells. In this study, we prepared PEG-PE cationic liposome to encapsulate adenovirus and confirmed that the resulting complex could enhance the transfection ability both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 93%
“…Simple mixing of adenoviral particles and cationic nanoparticles spontaneously produces complexes, and the Ad-nanoparticle complexes facilitate viral attachment to negatively charged cell membranes and increase gene transfer in both CAR-positive and CAR-negative cells. [7][8][9][10] The composition of a nanoparticle determines the ability of that nanoparticle to act as a carrier of chemicals and biologics. 11 The type and content of a cationic lipid and other components used to form cationic lipid-based nanoparticles can affect the surface charge, size, and structure of the nanoparticles, thereby varying the strength of the interactions between nanoparticles and viral particles.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 A very limited number of studies, however, have addressed this issue in adenoviral gene delivery. Compared with liposomes containing 1,2-dioleyloxy-3-trimethylammonium propane chloride as a cationic lipid (Lipofectin ® ), dioleoyltrimethylaminopropane (DOTAP)-containing liposomes were found to be more effective in enhancing adenovirus-mediated transgene expression, 7 emphasizing the importance of the of cationic lipid's chemical structure.…”
Section: Introductionmentioning
confidence: 99%